«Europe cannot be civilized»: colonialism and de-hispanification in Francisco Bilbao - Sanhueza, Marcelo (Revista de Historia Social y de las Mentalidades, 2024)
The article examines Francisco Bilbao’s essay "El Evangelio Americano" (1864) with respect to Bilbao’s criticism of European colonialist actions, as well as his displacement of the Old World as a unique paradigm of civilization and modernity. Within this framework, the author contends that Bilbao both portrays and rejects colonialism in the binary historical-cultural sense, since Bilbao alludes to the Hispanic past and to the South American present in the throes of European colonial interventions. Faced with this, Bilbao argues that in America an emancipation is developing that is not only political, but also cultural and intellectual, which is capable of freeing from oppression the disinherited, such as Native Americans, whom in his essay Bilbao transforms into agents of rebellion against history.